Palliative chemotherapy for gastroesophageal cancer in old and very old patients: a retrospective cohort study at the National Center for Tumor Diseases, Heidelberg - Berger, Anne Katrin; Zschäbitz, Stefanie; Jäger, Dirk; Haag, Georg Martin (World journal of gastroenterology, 2015)
AIM: To investigate the outcome of palliative chemotherapy in old patients with gastroesophageal cancer at the National Center for Tumor Diseases, Heidelberg., METHODS: Using a prospectively generated database, we retrospectively analyzed 55 patients ≥ 70 years under palliative chemotherapy for advanced gastroesophageal cancer at the outpatient clinic of the National Center for Tumor Diseases Heidelberg, Germany between January 2006 and December 2013. Further requirements for inclusion were (1) histologically proven diagnosis of gastroesophageal cancer; (2) advanced (metastatic or inoperable) disease; and (3) no history of radiation or radiochemotherapy. The clinical information included Eastern Cooperative Oncology Group performance status (ECOG PS), presence and site of metastases at diagnosis, date of previous surgery and perioperative chemotherapy, start and stop date of first-line treatment, toxicities and consecutive dosage reductions of first-line treatment, response to first-line therapy, date of progression, usage of second-line therapies and date and cause of death. Survival times [progression-free survival (PFS), overall survival (OS) and residual survival (RS)] were calculated. Toxicity and safety were examined. Prognostic factors including ECOG PS, age and previous perioperative treatment were analyzed., RESULTS: Median age of our cohort was 76 years. 86% of patients received a combination of two cytotoxic drugs. 76 percent of patients had an oxaliplatin-based first-line therapy with the oxaliplatin and 5-fluorouracil regimen being the predominantely chosen regimen (69%). Drug modifications due to toxicity were necessary in 56% of patients, and 11% of patients stopped treatment due to toxicities. Survival times of our cohort are in good accordance with the major phase III trials that included mostly younger patients: PFS and OS were 5.8 and 9.5 mo, respectively. Survival differed significantly between patient groups with low (≤ 1) and high (≥ 2) ECOG PS (12.7 mo vs 3.8 mo, P < 0.001). Very old patients (≥ 75 years) did not show a worse outcome in terms of survival. Patients receiving second-line treatment (51%) had a significantly longer RS than patients with best supportive care (6.8 vs 1.4 mo, P = 0.001). Initial ECOG PS was a strong prognostic factor for PFS, OS and RS., CONCLUSION: Old patients with non-curable gastroesophageal cancer should be offered chemotherapy, and ECOG PS is a tool for balancing benefit and harm upfront. Second-line treatment is reasonable.
Gesehen am /07.07.2017